2018
DOI: 10.2319/061917-399.12
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with open gingival embrasures after orthodontic treatment

Abstract: Objectives: To investigate the incidence of and contributing factors to open gingival embrasures between the central incisors after orthodontic treatment. Materials and Methods: One hundred posttreatment patients (29 men and 71 women; mean age, 24.7 years) were divided retrospectively into occurrence and nonoccurrence groups based on intraoral photographs. Based on the severity, the occurrence group was further divided into mild, moderate, and severe groups. Parameters from periapical radiographs, superimposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 16 publications
2
35
0
1
Order By: Relevance
“…Studies have reported a 98% presence of the interdental papilla when this distance was 5 mm or less, 56% presence at a distance of 6 mm and only 27% presence at a distance of 7 mm [30]. More recent studies are in agreement with this finding [4,11,20,22]. This study revealed that the height between crestal alveolar bone and the incisal contact point before and after treatment including SARME in the group with recession was lower compared to the group with recession, though this difference was just short of reaching statistical significance.…”
Section: Discussionsupporting
confidence: 60%
“…Studies have reported a 98% presence of the interdental papilla when this distance was 5 mm or less, 56% presence at a distance of 6 mm and only 27% presence at a distance of 7 mm [30]. More recent studies are in agreement with this finding [4,11,20,22]. This study revealed that the height between crestal alveolar bone and the incisal contact point before and after treatment including SARME in the group with recession was lower compared to the group with recession, though this difference was just short of reaching statistical significance.…”
Section: Discussionsupporting
confidence: 60%
“…At this step, 14 articles were nominated ( Figure 1 ) for full-text reading, which led to the exclusion of the other nine articles [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], and the reasons for excluding these records are summarized in Table 1 . Finally, five articles [ 1 , 10 , 13 , 41 , 42 ] fulfilling the eligibility criteria were further analyzed for data extraction and answering the PEO question. The computed Cohen’s kappa values for inter-reviewer agreement for the title/abstract and full-text screening procedure were 0.83 and 0.89, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…GBT (also called “open gingival embrasure”) is formed due to the loss of interdental papilla [ 9 ]. In addition, GBT may cause periodontal problems due to food retention and potential difficulty in mechanical plaque control [ 10 ]. Therefore, the prevention of GBT formation by preserving the interdental papilla, especially in the esthetic zone, must be considered during OT [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lygiai toks pat tarpdantinių dantenų dimensijos pokytis stebimas ortodontiškai gydant susigrūdusius, persidengusius kandžius -kai dantys ištiesinami, buvusi dantenų spenelio morfologija (siauras, ilgas spenelis) nebeatitinka gydymu pasiekto naujo kontakto tarp dantų tipo (spenelis lieka per trumpas) [30]. Ortodontinio gydymo plano žingsniai -AŽ kandžio pašalinimas arba intruzija, VŽ centrinių kandžių judėjimas liežuvio kryptimi ar dantų judesys lūpų kryptimi -laikomi ATK atsiradimą predisponuojančiais ortodontijos etapais [31][32][33]. Planuojant ortodontinį gydymą, dėmesį reikėtų atkreipti į trikampio formos priekinių dantų vainikus (tokiems esant, būdingos diverguojančios šaknys, ilgesnis tarpdantinis tarpas bei didesnis atstumas tarp alveolinio kaulo keteros ir dantų kontaktinio taško), ploną dantenų biotipą (šis nepasižymi gausia kraujotaka ir gera audinio "atmintimi" veikiant išorinėms, t.y.…”
Section: Tyrimo Rezultatai Ir Diskusijaunclassified